Interoceptive attention in opioid and stimulant use disorder. (16th October 2019) - Stewart, Jennifer L.; Khalsa, Sahib S.; Kuplicki, Rayus; Puhl, Maria; T1000 Investigators,; Paulus, Martin P.
Abstract: Blunted anterior insula activation during interoceptive perturbations has been associated with stimulant (cocaine and amphetamine) use disorder (SUD) and is related to risk for and prognosis of SUD. However, little is known whether these interoceptive alterations extend to opioid use disorder (OUD). This exploratory study used the same experimental probe during functional magnetic resonance imaging (fMRI) to test the hypothesis that SUD and OUD exhibit interoceptive discrepancies characterized by subjective ratings and activation within the insula. Recently, abstinent individuals diagnosed with current SUD (n = 40) or current OUD (n = 20) were compared with healthy individuals (CTL; n = 30) on brain and self‐report responses during an interoceptive attention task known to elicit insula activation. Participants selectively attended to interoceptive (heartbeat and stomach) and exteroceptive signals during blood‐oxygen‐level‐dependent fMRI recording. Groups and conditions were compared on (a) activation within probabilistic cytoarchitectonic segmentations of the insula and (b) self‐reported stimulus intensity. First, SUD showed amplified ratings of heart‐related sensations but attenuation of dorsal dysgranular insula activity relative to CTL. Amplified ratings were linked to drug use recency, while attenuation was normalized with greater past‐year stimulant use. Second, SUD and OUD showed attenuation of dorsal dysgranular insula activity during attention to stomach sensations relative to CTL. Taken together, these results are consistent with altered neural processing of interoceptive signals in drug addiction, particularly as a function of SUD. Future studies will need to determine whether interoceptive metrics help to explain substance use disorder pathophysiology and are useful for predicting outcomes. Abstract : Substance use involves the repeated modulation of interoceptive signals in the body and associated brain circuits. In this study, we found that individuals with stimulant use disorders (SUD) show amplified ratings of heart‐related sensations but attenuation of insula activity relative to controls. Amplified sensation ratings were linked to drug use recency, while insula attenuation was linked to a number of past‐year stimulant uses. These results provide evidence of an abnormal neural processing of interoceptive signals in drug addiction.